2022
DOI: 10.3389/fpls.2022.953225
|View full text |Cite
|
Sign up to set email alerts
|

Division of cortical cells is regulated by auxin in Arabidopsis roots

Abstract: The root cortex transports water and nutrients absorbed by the root epidermis into the vasculature and stores substances such as starch, resins, and essential oils. The cortical cells are also deeply involved in determining epidermal cell fate. In Arabidopsis thaliana roots, the cortex is composed of a single cell layer generated by a single round of periclinal division of the cortex/endodermis initials. To further explore cortex development, we traced the development of the cortex by counting cortical cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Auxin has been shown to have a strong impact on the regulation of cell 20 shape and division through modulation of the cytoskeleton (Vaddepalli et al, 2021;García-González & van Gelderen, 2021). In line with these observations, a recent study has shown that activation of cortical auxin response induces anticlinal and periclinal cell divisions, as well as abnormal root hair patterning (Kim et al, 2022). While our pDR5::SAND auxin response marker showed no activation in the cortex of pcp-1, we observed that cortical cell morphology and root hair density was partially rescued in response to auxinole, while root hair density increased in response to IAA in Col-0 at 16°C.…”
Section: Discussionmentioning
confidence: 88%
“…Auxin has been shown to have a strong impact on the regulation of cell 20 shape and division through modulation of the cytoskeleton (Vaddepalli et al, 2021;García-González & van Gelderen, 2021). In line with these observations, a recent study has shown that activation of cortical auxin response induces anticlinal and periclinal cell divisions, as well as abnormal root hair patterning (Kim et al, 2022). While our pDR5::SAND auxin response marker showed no activation in the cortex of pcp-1, we observed that cortical cell morphology and root hair density was partially rescued in response to auxinole, while root hair density increased in response to IAA in Col-0 at 16°C.…”
Section: Discussionmentioning
confidence: 88%
“…We also identified RBOHD enriched in endodermal cells where is known to activate ROS-dependent signaling to help CS formation 49,50 . Conversely, ARF5 is enriched in the cortex, expression of this gene in the cortex can drive cortical cell division 51 . At the same time, we found the cochaperone P23-1 enriched in cortex, where it has been reported to be crucial for auxin distribution and proper number of cortical cells 52,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, NPY5/MEL1 is enriched in endodermal cells, where it has been reported to control PIN1 subcellular basal localization and root gravitropic response 48 . Conversely, ARF5 is enriched in the cortex, expression of this gene in the cortex can drive cortical cell division 49 . At the same time, we found TT7 enriched in cortex, where it has been reported to control anthocyanin-dependent auxin flux by altering the expression of PIN1 auxin transporter 50,51 .…”
Section: Resultsmentioning
confidence: 99%
“…The water and nutrients absorbed by the root epidermis are transported by the cortex, located between the root epidermis and the endodermis, into the vascular bundle by apoplastic and symplastic routes, and are involved in determining the fate of epidermal cells. 80 The cortex in plants is a relatively undifferentiated cell type called ground tissue. Although the cortex layers vary among species, they remain almost unchanged at a particular developmental stage for a specific species.…”
Section: Flow-modulated Mechanical Stress Versus Nutrient Uptakementioning
confidence: 99%